Size exclusion chromatography characterization of poly (ether ether ketone), PEEK, after chemical modification - Aboelanin, Hamza Mahmoud; Arndt, Jan-Hendrik; Macko, Tibor; Podzimek, Štěpán; Bruell, Robert (Wiley-Blackwell, 2023)
Characterization of the molar mass distribution (MMD) of poly (ether ether ketone) (PEEK) is very troublesome due to the insolubility of PEEK in common solvents. The solubility of PEEK may be substantially improved after its sulfonation. Sulfonated PEEK (SPEEK) was prepared by sulfonation of PEEK with 98% concentrated H2SO4 at room temperature. The presence of sulfonic acid group (-SO3H) in PEEK matrix was confirmed by nuclear magnetic resonance and Fourier transform infrared spectroscopy. The degree of sulfonation (DS similar to 95%) was determined by proton nuclear magnetic resonance in deuterated dimethyl sulfoxide and by thermal analysis methods. The equivalent molar mass and MMD of sulfonated PEEK was determined at 30 degrees C in three polar solvents (N,N-dimethylacetamide, N,N-dimethylformamide N-methyl-2-pyrollidone) in PS/DVB column using calibration with PMMA standards. A salt (LiBr) was added to the solvents for suppression of undesired interactions of analytes with the column packing. Moreover, the sulphonated PEEK was separated with size exclusion chromatography (SEC) coupled to a multi-angle light scattering (MALS) detector. It was found that the absolute average molar mass of SPEEK from the MALS detection is much closer to the value measured by SEC in N,N-dimethylacetamide +LiBr than the values determined in N,N-dimethylformamide and N-methyl-2-pyrollidone.
GPC charakterizace poly(ether ether ketonu), PEEK, po chemické modifikaci
Keywords: engineering polymers; PEEK; size exclusion chromatography; GPC; technické polymery; PEEK